Survey of Running Speed and Limb Muscle Explosive Power in Students SMP Negeri 2 Madang Suku III - Hidayat, Ahmad; Akhbar, M Taheri; Kristina, Putri Cicilia (Yayasan Sembilan Pemuda Indonesia, 2023)
This research is motivated by the high potential of long jump athletics to be a positive activity and opportunity for students to achieve achievements at SMP Negeri 2 Madang Suku III. The problem in this study was that there had never been tests and evaluations before regarding the physical condition of students which affected the results of long jumps such as running speed and leg muscle explosive power. Therefore, researchers need to conduct a survey regarding the ability to run speed and explosive power of the leg muscles so that the coach or teacher understands the lack of physical condition and can improve the training program that will be given to students. The purpose of this study was to examine and survey the ability of running speed and muscle explosive power of students of SMP Negeri 2 Madang TRIPS III. The research design is in the form of descriptive statistics with a total of 25 students as subjects. The ice instrument uses a 30-meter run test and a vertical jump test. Furthermore, the data were analyzed using descriptive statistical techniques in the form of mean, mode, standard deviation, and coefficient of variance. From the data analysis, two conclusions were obtained, namely (1) the results of the 30-meter running speed test obtained 20% (5 people) in the very good category, and 48% (12 people) in the good category. 32% (8 people) category is poor. (2) the results of the leg muscle explosive power test obtained 4% (1 person) in the very good category, 40% (10 people) in the good category, and 56% (14 people) in the poor category. Based on the results of the study, it can be concluded that the average running speed of students at SMP Negeri 2 Madang Suku III is in a good category. While the explosive power ability of the leg muscles of students of SMP Negeri 2 Madang Suku III on average is in the poor category.